Casting mold and continuous casting method of steel
Patent Information
- Application Number
- JP2024128787
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-24
- Filing Date
- 2024-08-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-08-05
AI Technical Summary
【0010】 本発明に係る鋳型は、従来の鋳型よりも高温下での溶融モールドフラックスとの濡れ性が高く、溶融モールドフラックスとの接触角が小さくなるので、溶融モールドフラックスの不均一流入を抑制できる。これにより、溶融モールドフラックスと鋳型との間にエアギャップ層が形成されることが抑制され、溶鋼の凝固不均一を抑制できる。また、鋳型内で潤滑剤の役割を担う溶融モールドフラックスが溶鋼と鋳型の間に流入しやすくなるので、凝固シェルと鋳型との焼き付きが抑制され、鋼の高速連続鋳造の安定操業が実現できるようになる。さらに、エアギャップ層が形成されることを抑制することで鋳型抜熱量が増加するので、鋳造速度を向上させて鋳型の生産能力を向上できるようになる。
Smart Images

Figure 2025031590000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a mold used in continuous casting of steel and a method for continuous casting of steel using the mold. [Background technology]
[0002] In continuous casting, increasing the casting speed is essential to improve productivity, but there are problems such as burning of the solidified shell due to insufficient mold flux consumption and uneven solidification due to uneven inflow of mold flux. When uneven inflow of mold flux occurs, an air gap layer with low thermal conductivity is formed between the mold flux and the mold, and heat removal from the molten steel is partially reduced. This creates areas of the molten steel where the amount of heat removal is high and areas where it is low, resulting in uneven solidification of the solidified shell. When the problem of uneven solidification occurs, surface defects such as vertical cracks occur in the slabs produced by continuous casting. Furthermore, in addition to the above problems during high-speed casting, medium carbon steels such as hypoperitectic steels tend to have even greater problems of uneven solidification because the volume change due to δ / γ transformation during solidification is large.
[0003] To address these problems, Patent Document 1 discloses a mold for continuous casting in which the surface of the mold that comes into contact with molten steel is coated with an amorphous alloy made of an iron alloy or nickel alloy. According to Patent Document 1, applying this coating can impart high wear resistance to the mold, which can result in smooth continuous casting of steel and a longer mold life.
[0004] Patent Document 2 discloses a mold in which dissimilar conductive metal filled parts, in which the surface of the mold that comes into contact with molten steel is filled with a metal having a thermal conductivity different from that of the mold, are regularly provided. According to Patent Document 2, by providing the dissimilar conductive metal filled parts to periodically increase and decrease the thermal resistance of the mold, the stress caused by the phase transformation of the solidified shell is reduced, and deformation of the solidified shell is reduced, thereby making it possible to suppress uneven solidification of the solidified shell. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2001-105103 A [Patent Document 2] JP 2017-24079 A Summary of the Invention [Problem to be solved by the invention]
[0006] In the mold for continuous casting disclosed in Patent Document 1, the surface facing the casting space is coated with a molten layer of an amorphous alloy, but the coating has low wettability with the molten mold flux. Therefore, when the molten mold flux does not easily flow between the molten steel and the mold under high-speed casting conditions, seizure occurs between the mold and the solidified shell. In addition, even under normal casting conditions, the wettability of the coating with the molten mold flux is low, so that the molten mold flux flows in unevenly, forming an air gap layer and causing uneven solidification of the molten steel.
[0007] In addition, the mold in which the dissimilar conductive metal filling parts are regularly provided as disclosed in Patent Document 2 also has low wettability with the molten mold flux, and thus there are problems such as sticking between the mold and the solidified shell and non-uniform solidification of molten steel due to the formation of an air gap layer. In addition, there is also a problem that the effect of reducing deformation of the solidified shell by providing the dissimilar conductive metal filling parts is reduced when an air gap layer is formed.
[0008] Furthermore, the formation of the air gap layer reduces the amount of heat removed from the mold, making it difficult to increase the casting speed and improve the production capacity of the mold. The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a mold that can improve wettability with molten mold flux and suppress the formation of an air gap layer, and a method for continuous casting of steel using the mold. [Means for solving the problem]
[0009] The means for solving the above problems are as follows. [1] A mold used in continuous casting of steel, comprising a plurality of mold copper plates, the mold's surface in contact with molten steel is covered with a coating containing one or more of metal carbides, metal nitrides, and metal carbonitrides, and a dissimilar material filled section is provided beneath the coating, the dissimilar material filled section being filled with a metal or non-metal having a different thermal conductivity from that of the mold copper plates. [2] The mold according to [1], wherein the coating contains 20% by mass or more of a metal selected from the group consisting of one of Ni, Cr, Co, and Fe, or an alloy selected from two or more of these metals. [3] The mold according to [1] or [2], wherein the thickness of the coating is 50 μm or more and 10 mm or less. [4] A method for continuous casting of steel, comprising continuously casting steel using the mold according to any one of [1] to [3]. Effect of the Invention
[0010] The mold according to the present invention has higher wettability with molten mold flux at high temperatures than the conventional mold, and the contact angle with the molten mold flux is smaller, so that the non-uniform inflow of the molten mold flux can be suppressed. This suppresses the formation of an air gap layer between the molten mold flux and the mold, and suppresses non-uniform solidification of the molten steel. In addition, the molten mold flux, which acts as a lubricant in the mold, is easily able to flow between the molten steel and the mold, so that the seizure between the solidified shell and the mold is suppressed, and stable operation of high-speed continuous casting of steel can be realized. Furthermore, the suppression of the formation of an air gap layer increases the amount of heat removed from the mold, so that the casting speed can be increased, and the production capacity of the mold can be improved. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a continuous casting facility having a mold according to this embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing a part of the mold. [Diagram 3] FIG. 3 is an enlarged view of part A in FIG. [Figure 4] FIG. 4 is a graph showing the relationship between the TiC content and the contact angle with the molten mold flux for each metal. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described below through the embodiments of the present invention. The following embodiments are preferred examples of the present invention, and the present invention is not limited to these embodiments.
[0013] FIG. 1 is a schematic cross-sectional view showing an example of a continuous casting equipment 10 having a mold 12 according to the present embodiment. The continuous casting equipment 10 has the mold 12, a tundish 14 installed above the mold 12, and a plurality of slab support rolls 16 arranged below the mold 12. Although not shown in the figure, a ladle for accommodating molten steel 18 is installed above the tundish 14, and the molten steel 18 is poured into the tundish 14 from the bottom of the ladle. An immersion nozzle 20 is installed at the bottom of the tundish 14, and the molten steel 18 is poured into the mold 12 through the immersion nozzle 20. The molten steel 18 is solidified by extracting heat from the inner surface of the mold 12, and a solidified shell 24 is formed. As a result, a slab 28 is formed having the solidified shell 24 as an outer shell and an unsolidified layer 26 made of the molten steel 18 inside.
[0014] In the gaps between adjacent strand support rolls 16 in the casting direction, a plurality of secondary cooling zones 30 each equipped with spray nozzles (not shown) are installed along the casting direction from directly below the mold 12. The strand 28 is cooled as it is pulled out by cooling water sprayed from the spray nozzles in the secondary cooling zones 30. While the strand 28 is transported by the strand support rolls 16 and passes through the plurality of secondary cooling zones 30, the solidified shell 24 is appropriately cooled, and solidification of the unsolidified layer 26 proceeds until solidification of the strand 28 is completed.
[0015] Downstream in the casting direction, a plurality of transport rolls 17 are installed for continuing to transport the slab 28. A slab cutter 32 for cutting the slab 28 is disposed above the transport rolls 17. After solidification is complete, the slab 28 is cut by the slab cutter 32 into slabs 28a of a predetermined length. In this manner, the slab 28a, which is steel, is continuously cast using the continuous casting equipment 10.
[0016] FIG. 2 is a schematic cross-sectional view showing a part of the mold 12. The mold 12 is composed of four mold copper plates 13 that are combined to form a substantially rectangular tube shape according to the shape of the cast piece to be cast. The inner surfaces (surfaces that come into contact with the molten steel 18) of the four mold copper plates 13 are covered with a coating 22. Under the coating 22, a dissimilar substance-filled portion 23 is provided on the inner surface of the mold copper plate, which is filled with a metal or nonmetal having a thermal conductivity different from that of the mold copper plate. The dissimilar substance-filled portion 23 is formed, for example, by filling a circular groove independently machined on the inner surface of the mold copper plate 13 with a metal or nonmetal. The filling thickness of the dissimilar substance-filled portion 23 is preferably 50 μm or more. The filling means may be a plating process or a thermal spraying process, or a metal and a nonmetal that match the shape of the circular groove may be fitted into the circular groove to fill it.
[0017] The upper surface of the molten steel 18 in the mold 12 is covered with molten mold flux 19 (hereinafter, referred to as molten mold flux 19). The molten mold flux 19 flows between the mold 12 and the molten steel 18 and serves as a lubricant. The molten mold flux, which serves as a lubricant, flows between the mold 12 and the molten steel 18, thereby suppressing seizure between the mold 12 and the solidified shell 24. The molten steel 18 is injected into the mold 12 through the submerged nozzle 20 while covered with the molten mold flux 19. The molten steel 18 injected into the mold 12 is cooled by the mold 12. As a result, the molten steel 18 at the interface between the mold 12 and the molten steel 18 solidifies, and a solidified shell 24 is formed.
[0018] In the cooling of the molten steel 18 by the mold 12, if the molten mold flux 19 flows non-uniformly between the mold 12 and the molten steel 18, an air gap layer with low thermal conductivity is formed in the area where the molten mold flux 19 does not flow, and the amount of heat removed from the molten steel 18 is reduced. If there is an area where the amount of heat removed is partially reduced, the solidification of the molten steel 18 in contact with the area is delayed, resulting in a problem of non-uniform solidification. Furthermore, since the molten mold flux 19 serves as a lubricant, in the area where the molten mold flux 19 does not flow and an air gap layer is not formed, there is a risk of seizure between the mold 12 and the solidified shell 24.
[0019] In contrast, in the mold 12 according to the present embodiment, the inner surface of the mold copper plate 13 that comes into contact with the molten steel 18 is coated with a coating 22 containing one or more of metal carbides, metal nitrides, and metal carbonitrides. This improves the wettability between the inner surface of the mold copper plate 13 and the molten mold flux 19 at high temperatures, suppressing uneven inflow of the molten mold flux 19. As a result, it is possible to suppress the generation of air gaps due to uneven inflow of the molten mold flux 19 in the early stage of solidification of the molten steel 18, and the uneven growth and vertical cracks of the slab due to uneven thermal resistance between the mold and the molten steel caused by the air gaps. Furthermore, it is possible to reduce the risk of seizure between the mold 12 and the solidified shell 24.
[0020] Fig. 3 is an enlarged view of part A in Fig. 2. As shown in Fig. 3, a dissimilar material filled section 23 filled with a metal or nonmetal having a thermal conductivity different from that of the mold copper plate is provided under the coating 22. By providing the dissimilar material filled section 23, the thermal resistance of the mold can be periodically increased and decreased, and the stress due to the phase transformation of the solidified shell can be reduced. This reduces the deformation of the solidified shell, suppressing uneven solidification of the solidified shell, and dispersing the stress to reduce the amount of individual distortion, thereby suppressing the occurrence of surface cracks on the surface of the solidified shell.
[0021] In the mold 12 provided with the dissimilar-substance-filled portion 23, if the coating 22 is not provided, the molten mold flux 19 flows non-uniformly between the mold 12 and the molten steel 18, the above-mentioned effect is reduced, and the occurrence of surface cracks on the solidified shell surface cannot be suppressed. On the other hand, by providing the coating 22, the non-uniform flow of the molten mold flux 19 is suppressed at high temperatures, and the above-mentioned effect of providing the dissimilar-substance-filled portion 23 makes it possible to suppress the occurrence of surface cracks on the solidified shell surface.
[0022] The coating 22 is provided for the purpose of suppressing non-uniform flow of the molten mold flux 19 into the dissimilar substance filled portion 23. For this reason, the entire inner surface of the mold copper plate 13 does not need to be covered with the coating 22, and it is sufficient that at least the area where the dissimilar substance filled portion 23 is provided is covered with the coating 22.
[0023] The metal carbide, metal nitride, and metal carbonitride contained in the coating 22 may be, for example, one or more of TiC, SiC, ZrC, TiN, CrN, TiAlN, and TiCN. Among these, it is preferable to use TiC, which is a metal carbide. The content of the metal carbide, metal nitride, and metal carbonitride contained in the coating 22 is preferably 0.1 mass% or more and 80.0 mass% or less. If the content of the metal carbide, metal nitride, and metal carbonitride contained in the coating 22 is more than 80.0 mass%, it is not preferable because cracks may occur in the coating layer of the coating 22. If the content of the metal carbide, metal nitride, and metal carbonitride contained in the coating 22 is less than 0.1 mass%, it is not preferable because the effect of improving the wettability with the molten mold flux 19 is reduced.
[0024] Furthermore, the coating 22 preferably contains 20 mass % or more of a metal or an alloy of two or more of Ni, Cr, Co, and Fe. If the content of the metal or the alloy of two or more of Ni, Cr, Co, and Fe contained in the coating 22 is less than 20 mass %, it is difficult to form the coating 22, which is not preferable. Since the coating 22 contains at least 0.1 mass % of metal carbides, metal nitrides, and metal carbonitrides, the upper limit of the content of the metal or the alloy of two or more of Ni, Cr, Co, and Fe contained in the coating 22 is 99.9 mass %.
[0025] Furthermore, the coating 22 may contain unavoidably mixed impurities at 5 mass % or less. If the impurities are contained at 5 mass % or less, the wettability with the molten mold flux 19 is not affected.
[0026] The thickness of the coating 22 is preferably 50 μm or more and 10 mm or less. By making the thickness of the coating 22 50 μm or more and 10 mm or less, the loss of the coating 22 due to wear can be suppressed, and the decrease in the amount of heat removed from the mold 12 can be suppressed, and a solidified shell thickness that allows continuous casting can be ensured. On the other hand, if the thickness of the coating 22 is less than 50 μm, there is a risk that part of the coating 22 will be lost due to wear, which is not preferable. Also, if the thickness of the coating 22 is made thicker than 10 mm, the amount of heat removed from the mold 12 decreases, and the solidified shell thickness becomes thin, making it difficult to cast a slab, which is not preferable. The thickness of the coating 22 is more preferably 0.1 mm or more and 0.3 mm or less. By making the thickness of the coating 22 0.1 mm or more and 0.3 mm or less, the loss of the coating 22 due to wear and the decrease in the amount of heat removed from the mold 12 can be further suppressed. Also, the thickness of the foreign material filling portion 23, including the thickness of the coating 22, is preferably 10 mm or less. This suppresses the decrease in the amount of heat removed from the mold 12, and ensures a solidified shell thickness that allows continuous casting.
[0027] The method for covering the mold copper plate 13 with the coating 22 is not particularly limited, but for example, the contact surface of the mold copper plate 13 that comes into contact with the molten steel 18 may be covered with the coating 22 by using laser build-up welding.
[0028] Next, a description will be given of the experimental results which confirmed that covering the mold copper plate 13 with the coating 22 improves the wettability with the molten mold flux 19 at high temperatures. In invention example 1, a powder material in which TiC powder and Inconel powder are mixed in a ratio of 20 mass % and 80 mass % was laser build-up welded onto a metal piece having an area of 10 mm x 10 mm, to produce a test piece covered with a coating having a thickness of 0.2 mm.
[0029] In Example 2, a test piece coated with a 0.2 mm thick coating was produced by laser build-up welding a powder material made of a mixture of 50% TiC powder and 50% Ni powder to a metal piece of the same size. In Example 3, a test piece coated with a 0.2 mm thick coating was produced by laser build-up welding a powder material made of a mixture of 50% TiC powder and 50% Co powder to a metal piece of the same size. In Example 4, a test piece coated with a 0.2 mm thick coating was produced by laser build-up welding a powder material made of a mixture of 50% TiC powder and 50% Fe powder to a metal piece of the same size.
[0030] In invention example 5, a powder material made by mixing 0.1 mass% TiC powder and 99.9 mass% Ni powder was sprayed onto a metal piece of the same size to prepare a test piece coated with a 0.2 mm thick coating. In invention example 6, a metal piece of the same size was sprayed with TiC powder to prepare a test piece coated with a 0.2 mm thick coating. In invention example 7, a metal piece of the same size was sprayed with TiN powder to prepare a test piece coated with a 0.2 mm thick coating. Meanwhile, in conventional example 1, a test piece was prepared by plating a 0.2 mm thick Ni-Co (Ni:Co=50:50) coating onto a metal piece of the same size.
[0031] A mold flux of 2 mm square was placed on the test pieces of the invention examples 1 to 6 and the conventional example 1, and the temperature was raised from room temperature in a point-focusing infrared image furnace. The mold flux used in the experiment was mainly composed of SiO2: 30 mass%, Al2O3: 5 mass%, CaO: 30 mass%, and also contained MgO, Na2O, and LiO2. The basicity of the mold flux (CaO / SiO2) was 1. While taking a video of the state inside the furnace, the temperature of the mold flux was raised to 1000°C, melted and turned into droplets, and the contact angle between the droplets of the molten mold flux and the test pieces was measured. The measurement results of the contact angle are shown in Table 1 below.
[0032] [Table 1]
[0033] As shown in Table 1, the contact angle between the Ni-Co plating coating of the conventional example and the molten mold flux was 59°. In contrast, the contact angles between the coating of Experimental Examples 1 to 7 containing metal carbide or metal nitride and the molten mold flux were all smaller than those of the conventional examples. From this result, it was confirmed that the wettability with the molten mold flux at high temperatures can be improved more than before by covering the contact surface of the mold copper plate 13 with the molten steel 18 with a coating containing metal carbide or metal nitride. It is presumed that the improvement in wettability with the molten mold flux is due to the fact that the reactivity between the molten mold flux and the coating material is improved by the metal carbide or metal nitride distributed on the mold surface, and the surface tension between the molten mold flux and the mold is reduced. Note that the same effect can be expected with metal carbonitride, so it is considered that the wettability with the molten flux can be improved more than before by covering the contact surface of the mold copper plate 13 with the molten steel 18 with a coating containing metal carbonitride. Furthermore, since the reactivity between the molten mold flux and the coating material is improved regardless of the composition of the mold flux, the above-mentioned effects can be obtained similarly regardless of the composition of the mold flux.
[0034] Next, the influence of the content of metal carbide and metal contained in the coating 22 will be described. Test pieces covered with a coating having a thickness of 0.2 mm were prepared using a powder material obtained by mixing TiC powder with Ni powder, Fe powder, Co powder, or Inconel powder in a predetermined ratio. Mold flux was placed on these test pieces, and the mold flux was melted by increasing the temperature from room temperature in a focused infrared image furnace to form droplets, and the contact angle of the droplet-shaped molten mold flux with the test pieces was measured. The measurement results of the contact angle are shown in Table 2 below. The mold flux used is mainly composed of SiO2: 30 mass%, Al2O3: 5 mass%, and CaO: 30 mass%, and also contains MgO, Na2O, and LiO2. The basicity (CaO / SiO2) of the mold flux is 1.
[0035] [Table 2]
[0036] Fig. 4 is a graph showing the relationship between the TiC content for each metal and the contact angle with molten mold flux, and is a graph of Table 2. In Fig. 4, the horizontal axis is the TiC content (mass%), and the vertical axis is the contact angle with mold flux (°). As shown in Fig. 4, among Ni, Fe, Co, and Inconel, the coating using Ni or Inconel had a smaller contact angle with molten mold flux at high temperatures than the coating using Fe or Co. From this result, it can be seen that, among Ni, Fe, Co, and Inconel, it is preferable to use Ni or Inconel as the metal to be mixed with TiC.
[0037] Furthermore, when Ni or Inconel is used, it is preferable that the TiC content is 10 mass% or more and 80 mass% or less. This makes it possible to reduce the contact angle with the molten mold flux at high temperatures to 30° or less. When Ni or Inconel is used, it is more preferable that the TiC content is 20 mass% or more and 60 mass% or less. This makes it possible to reduce the contact angle with the molten mold flux at high temperatures to 20° or less.
[0038] Furthermore, when Ni or Inconel is used, it is found that the contact angle with the molten mold flux at high temperatures can be further reduced by setting the TiC content to 20% by mass or more and 40% by mass or less. From this result, it is found that when Ni or Inconel is used as the metal to be mixed with TiC, it is even more preferable to set the TiC content to 20% by mass or more and 40% by mass or less.
[0039] As described above, the mold 12 according to the present embodiment has high wettability with the molten mold flux 19, and the contact angle with the molten mold flux 19 is small. This allows the molten mold flux 19 to flow uniformly between the molten steel 18 and the mold 12, suppressing uneven flow of the molten mold flux 19. As a result, the formation of an air gap layer between the molten mold flux 19 and the mold is suppressed, and uneven solidification of the molten steel can be suppressed. In addition, since the seizure between the solidified shell and the mold is suppressed and the amount of heat removal from the mold is increased, stable operation of high-speed continuous casting can be realized by continuously casting steel using the mold. Furthermore, by using the mold 12 according to the present embodiment, it is possible to obtain an effect of suppressing the occurrence of surface cracks on the solidified shell surface due to the provision of the foreign material filling portion 23.
[0040] In the present embodiment, an example has been shown in which all the inner surfaces of the four mold copper plates 13 constituting the mold 12 are covered with the coating 22 and the dissimilar substance filled portion 23 is provided under the coating 22, but the present invention is not limited to this. It is sufficient that the inner surface of at least one of the four mold copper plates constituting the mold is covered with the coating 22 and provided with the dissimilar substance filled portion 23. By using a mold constituted by such mold copper plates, it is possible to suppress non-uniform solidification of the molten steel and to suppress seizure between the solidified shell and the mold, compared to the case in which all the inner surfaces of the four mold copper plates are covered with the coating 22 and a mold not provided with the dissimilar substance filled portion 23 is used. EXAMPLES
[0041] Test casting of medium carbon steel (chemical composition: C: 0.08-0.17% by mass, Si: 0.10-0.30% by mass, Mn: 0.50-1.20% by mass, P: 0.010-0.030% by mass, S: 0.005-0.015% by mass, Al: 0.020-0.040% by mass) was carried out at a casting speed of 2.3 m / min using the same mold flux as that used in the experiment to confirm the contact angle. A circular recess with a diameter of 5 mm was made on the surface of the continuous casting mold, and a heterogeneous material filling section filled with Ni to a maximum thickness of 1 mm was provided in the recess. This was then coated with a coating of 20% by mass TiC-80% by mass Inconel (Example 11), 50% by mass TiC-50% by mass Ni (Example 12), 50% by mass TiC-50% by mass Co (Example 13), and 50% by mass TiC-50% by mass Fe (Example 14). The thicknesses of the coatings were 0.1 mm, 0.2 mm, 0.5 mm, 1.0 mm, 25.0 mm, 10.0 mm, 15.0 mm, and 20.0 mm. Conventional Example 11 was a mold in which a circular recess with a diameter of 5 mm was provided on the surface of the mold, and the recess was filled with Ni to a maximum thickness of 1 mm.
[0042] The number of vertical cracks in the slabs cast using the molds under each condition was measured, and the number of vertical cracks was calculated by dividing the slab area (1 m 2The vertical crack density was calculated by dividing the vertical crack density of the slab cast using the continuous casting mold of Conventional Example 11 by the vertical crack density of the slab cast using each mold, as shown in Table 3. The number of vertical cracks in the slabs was measured by penetrant inspection.
[0043] [Table 3]
[0044] In Table 3, values less than 1.00 indicate that the vertical cracks in the slab were reduced and the slab quality was improved compared to the conventional mold filled with Ni as the dissimilar material filling portion, while values greater than 1.00 indicate that the vertical cracks in the slab were increased and the slab quality was deteriorated compared to the conventional mold filled with Ni.
[0045] As shown in Table 3, all of the slabs cast using the molds of Examples 11 to 14 had a value less than 1.00. The coatings of Examples 11 to 14 have the same composition as the coatings of Examples 1 to 4 shown in Table 1, and are coatings that have been confirmed to improve the wettability between the mold and the molten mold flux. These results confirm that improving the wettability between the mold and the molten mold flux reduces vertical cracks in the slab and improves the slab quality. Note that if the coating thickness is made thicker than 10 mm, the surface temperature of the mold becomes very high, the thickness of the solidified shell becomes thin, and casting of the slab becomes difficult, which is not preferable. [Explanation of symbols]
[0046] 10 Continuous casting equipment 12 Mold 13 Cast copper plate 14 Tundish 16. Cast piece support roll 17 Transport roll 18 Molten Steel 19 Molten mold flux 20 Submerged Nozzle 22 Coating 23 Foreign substance filling section 24 Solidified shell 26 Unsolidified layer 28 Castings 30 Secondary cooling zone 32 Slab cutting machine
Claims
1. A mold for continuous casting of steel, comprising a plurality of mold copper plates, A mold in which a molten steel contact surface of the mold is covered with a coating containing one or more of a metal carbide, a metal nitride, and a metal carbonitride, and a heterogeneous material filled portion filled with a metal or non-metal having a different thermal conductivity from that of the mold copper plate is provided under the coating.
2. The mold according to claim 1 , wherein the coating contains 20% by mass or more of a metal selected from the group consisting of Ni, Cr, Co, and Fe, or an alloy selected from two or more of these metals.
3. 3. The mold according to claim 1 or 2, wherein the coating has a thickness of 50 μm or more and 10 mm or less.
4. A method for continuous casting of steel, comprising the step of continuously casting steel using the mold according to claim 1 or 2.
5. A method for continuous casting of steel, comprising the step of continuously casting steel using the mold according to claim 3.
Citation Information
Patent Citations
Mold for continuous steel casting
JP1979004236A
Mold for continuous casting
JP1983081544A
Production of mold for continuous casting
JP1989233047A
Mold copper plate of mold for continuous casting and its manufacturing method
JP2004098072A
Continuous casting mold and continuous casting method for steel
JP2017024078A